The Role of Librarians in The Era of Society 5.0: Missing or Increasing Importance? - Richard Togaranta Ginting; Fransiska Timoria Samosir; Arthur Dwie Yurinda; Majidah; Augustine Uzoma Madu (Record and Library Journal, 2023)
Background of the Study:  The development of the era of society 5.0 made the library participate in this development. The library is a combination of virtual and physical space to meet users' information needs as a society 5.0. Purpose: This study  reviews the existence of libraries and librarians’ roles in the era of society 5.0, whether they are lost or survive in the new phase.  Method: This study used an explorative mothod, it employs a number of scientific procedures, including data collection from libraries, reading and taking notes, and transforming the results into narrative writing.. Findings: Libraries and Librarians continue to thrive in the development of the society 5.0 era Libraries, and librarians increasingly have a role. Library developments that can be developed in this area include robotics in libraries, Self-Service Services, Digital Libraries, Information Consulting Services, and Digital Consulting Services. Conclusion: Libraries and Librarians are still needed and essential in the era of society 5.0 in library development. Librarians must work scientially and ensure professionalism while carrying out their duties and functions in library development to meet society's 5.0 users.